Transient sinus bradycardia caused by hepatitis A virus: a case report - Onder Kilicaslan; Didem Kizmaz Isancli; Esmanur Fil; Ahmet Irdem; Adem Karbuz (SpringerOpen, 2022)
Abstract Background The most common cause of acute viral hepatitis is the hepatitis A virus (HAV). Millions of people are thought to be infected each year. It is transmitted either by the fecal-oral route or by consuming contaminated food. Extrahepatic complications, notably cardiologic ones, are infrequent. This case report was presented due to the development of HAV-related bradycardia without hypotension in an unvaccinated refugee patient. Case presentation A 9-year-old male presented with the complaint of jaundice and vomiting. There was no history of fever, diarrhea, or abdominal pain. A precise knowledge of suspected food intake is lacking. There was no pathological examination finding except jaundice. Total bilirubin, direct bilirubin, aspartate aminotransferase, and alanine aminotransferase levels were high. The coagulation test was normal. Anti-HAV-IgM/IgG was positive in the patient with suspicious viral hepatitis. In the follow-up, the heart rate decreased to 43 beats/min during sleep and 46 beats/min when awake. Cardiological examination and tests were within normal limits. Hypotension was not accompanied. In the follow-up, bradycardia and impaired liver function tests regressed. The patient was discharged on the 10th day. Conclusions Cardiologic complications are rare, and patients diagnosed with acute hepatitis A should be monitored. The most effective way of protection from the hepatitis A virus is vaccination.